Practice guidelines for management of uterine corpus cancer in Korea: a Korean Society of Gynecologic Oncology consensus statement - Kim, Ju-Hyun; Kim, Dae-Yeon; Kim, Junhwan; Noh, Joseph J; Hwang, Woo Yeon; Baek, Min-Hyun; Choi, Min Chul; Joo, Won Duk; Lee, Yong Jae; Suh, Dong Hoon; Kim, Yong Beom (Journal of gynecologic oncology, 2024)
The Korean Society of Gynecologic Oncology (KSGO) had been making an effort to standardize and enhance the quality of domestic uterine corpus cancer treatment by developing updated clinical practice guidelines in 2021. The KSGO revised the guidelines based on a literature search using 4 key elements: Population, Intervention, Comparison, and Outcome framework. These elements include the evaluation of the efficacy and safety of immune checkpoint inhibitor treatment in recurrent/advanced endometrial cancer patients who have failed platinum-based chemotherapy, as well as the effect of combined treatment with trastuzumab in patients with HER2/neu-positive endometrial cancer. Additionally, the guideline assessed the efficacy and safety of omitting lymph node dissection in low-risk endometrial cancer patients, investigated the effect of sentinel lymph node mapping in early-stage endometrial cancer surgery, addressed the outcome of chemoradiation therapy as a postoperative treatment in patients with advanced (stage III-IVA) endometrial cancer, and explored the impact of initial treatment with immune checkpoint inhibitors on survival in patients with advanced or recurrent endometrial cancer patients.